EXPLORING FACTORS OF STRESS LEVEL IN PARENTS OF CHILDREN WITH AUTISTIC SPECTRUM DISORDER - Stanojević, Nina; Nenadović, Vanja; Fatić, Saška; Stokić, Miodrag (Specijalna edukacija i rehabilitacija, 2017)
In addition to difficulties in social interaction and communication, children with autistic spectrum disorder (ASD) also exhibit behaviors that interfere with daily activities and are difficult to control, which can lead to disturbances in the household and extended family. The child’s limited social, emotional and communicative abilities, their unequal cognitive development and maladaptive behaviors are a source of stress for parents. The goal of our study was to assess the level of stress in parents of children with ASD in relation to gender, education, age of parents, the child’s age, and speech and language skills. A sample of this study consisted of 40 parents (20 mothers and 20 fathers) aged 21 to 56 years. All respondents were parents of children with ASD, of which 22 parents of children receiving treatment at the Institute for Experimental Phonetics and Speech Pathology „Djordje Kostic“ and 18 parents who are members of the Association of parents of children with autism. In this study, we used The Parental Stress Scale (Berry & Jones, 1995) to assess the level of stress among parents. The results show that there are no statistically significant differences in the level of stress in relation to parental sex, parental age, the child’s age and child’s expressive language development. We found a statistically significant effect of parental education level (p=0.005), child’s receptive language development (p=0.008), and child’s verbal communication development (p=0.015) on parental stress level. Parental lower education level, child’s inability to understand speech and undeveloped verbal communication of the child can lead to greater parental stress. The stress of parents can significantly complicate and slow down the process of child rehabilitation. It is important to know that it is equally necessary to support fathers and mothers, parents of all ages, parents of children of all ages and different speech and language skills and that particular attention should be given to parents with lower education.